Chlorogenic acid compounds from sweetpotato (Ipomoea batatas L.) leaves facilitate megakaryocyte differentiation and thrombocytopoiesis via PI3K/AKT pathway - Zhang, Yi; Zhao, Lu; Wang, Liping; Yue, Ruixue; Zhu, Hong; Zhang, Wenting; Sun, Jian; Zhang, Zifeng; Ma, Daifu (Frontiers in Pharmacology, 2024)
Idiopathic thrombocytopenic purpura (ITP) is an autoimmune disorder characterized by antiplatelet autoantibodies, thrombocytopenia, and bleeding, however, its treatment options are limited. In this study, a kind of active component, chlorogenic acid compounds (CGAs) from sweetpotato leaves was extracted out to explore its medicinal value and provide novel therapeutic strategies for the treatment of ITP. CGAs was isolated by ionic liquids-ultrasound (IL-UAE), which contains 6 isomers of chlorogenic acid with total purity of 95.69%. The thrombopoietic effect and mechanism of CGAs were investigated using in silico prediction and experimental validation. The changes of HEL cells morphology in volume and the increase in the total cell percentage of polyploid cells indicated that CGAs could promote megakaryocyte differentiation. Meanwhile, CGAs could promote platelet formation in a murine model of ITP, which was established by injection of antiplatelet antibody.Further quantitative proteomics analysis and western blot verification revealed that CGAs could activate PI3K/AKT signaling pathway, which confirmed the mechanism prediction. It suggested that CGAs may provide a novel therapeutic strategy that relies on the PI3K/AKT pathway to facilitate megakaryocyte differentiation and platelet production.